Heat transfer and flow analysis of Casson fluid enclosed in a partially heated trapezoidal cavity. (November 2019) - Hamid, M.; Usman, M.; Khan, Z.H.; Haq, R.U.; Wang, W.
Abstract: In this article, we are reporting the mechanism of natural convection flow in a partially heated trapezoidal cavity containing non-Newtonian Casson fluid. A non-Newtonian model of Casson fluid is used to develop the governing flow equations. The thermal control inside the enclosure is managed using the partially heated lower wall. Most physical and significant conditions are used at the inclined walls of the cavity to attain the performance of heat management and streamlines. The Galerkin finite element technique (GFEM) is adopted to examine the solution of dimensionless PDEs system. The thermal and flow fields are envisioned through isotherms and streamlines while the simulations are performed for flow and thermal fields via various ranges of Rayleigh number (10 4  ≤  Ra  ≤ 10 5.5 ), and different lengths of the heated part. Furthermore, outcomes are visualized for Nusselt number over the cavity wall under the influence of the Casson parameter. It is observed that as Casson fluid parameter decreases the velocities in x -direction and y -direction exhibit the dominant behavior. The influence of lower values of Casson fluid parameter on Nusselt number is significant at the middle of the cavity while the Nusselt number increases as increases the heated bottom wall in length. Graphical abstract: The purpose of the present article is to investigate the thermal management and natural convection flow in a partially heated trapezoidal cavity filled with Casson fluid. The simulations has been performed for various values of the Rayleigh number and the governing parameters. Unlabelled Image